High-solid epoxy coating and preparation method thereof
By introducing functionalized boron nitride and OMWCNT-Ce-sodium gluconate composites into epoxy coatings, a PA-MA/EDA network and a protective precipitation layer are formed, which solves the problem of insufficient weather resistance and corrosion resistance of high-solid epoxy coatings and improves the mechanical properties and adhesion of the coating.
Patent Information
- Application Number
- CN202511156525.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-08-19
AI Technical Summary
Traditional high-solid epoxy coatings have deficiencies in weather resistance, corrosion resistance and adhesion, and are prone to coating blistering, cracking and decreased adhesion in harsh environments.
Functionalized boron nitride/PA-MA/EDA hybrid materials and OMWCNT-Ce-sodium gluconate composites are combined with epoxy resin. The PA-MA/EDA network is used to improve the crosslinking density and flexibility, and the cerium ions loaded on the OMWCNTs are used to form a protective precipitation layer to enhance the corrosion resistance and weather resistance of the coating.
It significantly improves the mechanical properties, adhesion and anti-corrosion performance of the coating, enhances the flexibility and weather resistance of the coating, effectively prevents the penetration of moisture and corrosive media, and extends the life of the coating.
Smart Images

Figure CN120737702A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to a high-solid epoxy coating and a preparation method thereof. Background Art
[0002] Epoxy resins possess excellent adhesion, thermal stability, chemical resistance, and corrosion resistance, making them commonly used in adhesives, coatings, potting materials, and composite materials, particularly in the coatings industry. Traditional epoxy resin coatings are typically solvent-based, primarily containing large amounts of organic solvents such as toluene, n-butanol, and phthalates. Due to the low boiling point and high volatility of these organic solvents, the emission of large amounts of volatile organic compounds (VOCs) poses a serious environmental risk. Furthermore, during the curing process, solvent volatilization can create pores in the paint film, reducing its performance.
[0003] Therefore, the development of environmentally friendly coatings has become a key development direction for the coatings industry. These coatings primarily include powder coatings, water-based coatings, and high-solids coatings. Powder coatings require high pre-treatment and demanding application conditions; water-based coatings suffer from drawbacks such as brittleness, poor corrosion resistance, demanding drying conditions, and a short shelf life. High-solids coatings, still considered solvent-based, typically utilize reactive diluents to reduce organic solvent usage, thereby lowering VOC emissions, improving fluidity, and enhancing processability.
[0004] High-solids epoxy coatings often use bisphenol A epoxy resin as their primary raw material. However, due to the aromatic ether bonds in their molecular structure, they are susceptible to degradation and fracture under ultraviolet radiation in sunlight, resulting in poor weather resistance. In addition, the high solids content in high-solids epoxy coatings leads to higher viscosity. During the coating process, the higher viscosity makes the coating less flexible and brittle after curing. When used in alternating environments (for example, seawater in ballast tanks is pumped back and forth, and the environment alternates between dry and wet), the coating film will bubble and crack due to the intrusion of liquid media such as water, acid, alkali, and salt, resulting in a loss of protective properties of the coating film and further causing rusting of the substrate. In addition, because high-solids epoxy coatings are more polar than traditional epoxy resin coatings, they have poor wettability on substrates with poor surface treatment, resulting in poor adhesion to the substrate. Especially in the case of insufficient surface treatment, the coating film adhesion is easily reduced, which can cause the coating film to fall off.
[0005] Therefore, it is necessary to provide a high-solids epoxy coating and a preparation method thereof to solve the problems existing in the above-mentioned prior art. Summary of the Invention
[0006] In view of this, the present invention provides a high-solid epoxy coating and a preparation method thereof, which can achieve corrosion resistance and weather resistance while having good adhesion.
[0007] To achieve the above object, the present invention provides a method for preparing a high-solids epoxy coating, comprising the following steps: S1. Functionalized boron nitride is dispersed in water, ultrasonically treated, phytic acid is added and stirred, the temperature is increased, melamine and hexamethylenediamine are added and stirred, the precipitate is collected by centrifugation, and vacuum dried to prepare a boron nitride / PA-MA / EDA hybrid material; S2, adding the oxidized multi-walled carbon nanotubes into water for ultrasonic treatment, adding cerium nitrate hexahydrate and sodium gluconate, mixing, centrifuging to obtain a precipitate, and washing to obtain an OMWCNT-Ce-sodium gluconate composite material; S3. Add solid epoxy resin, active diluent and mixed solvent into the reactor, heat and stir, add liquid epoxy resin, boron nitride / PA-MA / EDA hybrid material, OMWCNT-Ce-sodium gluconate composite material and polycaprolactone, mix and stir, grind and disperse, add curing agent and stir evenly to obtain high-solid epoxy coating.
[0008] The present invention utilizes the interaction between the phosphate groups of phytic acid (PA) and the amino groups of melamine (MA) / hexamethylenediamine (EDA) to form a PA-MA / EDA network, thereby achieving in-situ orderly assembly of PA-MA / EDA on the surface of functionalized boron nitride, and ultimately preparing a boron nitride / PA-MA / EDA hybrid material; the interaction between the phosphate groups and the amino groups in the boron nitride / PA-MA / EDA hybrid material effectively increases the reactivity of the epoxy groups, thereby significantly increasing the cross-linking density of the coating. This high cross-linking density reduces pores and cracks in the coating and greatly improves the overall mechanical properties. The addition of hexamethylenediamine introduces flexible spacer chains, and the long-chain alkanes provide molecular chain flexibility, which can effectively alleviate the internal stress caused by excessive cross-linking density; in addition, the phosphate groups (PA) and the amino groups (MA, EDA) in the PA-MA / EDA network form dynamic ionic cross-linking bonds through electrostatic interaction or ionic bonds, which also imparts The overall material has a certain self-healing ability, reducing the risk of brittle cracking of the overall material; PA-MA / EDA enhances the interfacial bonding between the coating and the metal substrate through multidentate coordination, enabling it to exhibit excellent adhesion and be used in more demanding environments; boron nitride effectively fills the microscopic pore structure inside the epoxy resin. After surface modification of boron nitride, its compatibility with the organic matrix is improved, allowing it to be better dispersed in the organic matrix, penetrate the epoxy network, and hinder the crack propagation path. It also further enhances the physical barrier properties of the overall coating, effectively preventing moisture, gas and corrosive media from penetrating the substrate surface; in addition, the chelating ability of phytic acid in the boron nitride / PA-MA / EDA hybrid material can form a dense passivation film on the surface of the metal substrate, delaying corrosion-induced coating peeling, and the layered structure of the boron nitride / PA-MA / EDA hybrid material can reflect ultraviolet light, which helps to improve the corrosion resistance and weather resistance of the coating.
[0009] This method prepares an OMWCNT-Ce-sodium gluconate composite by modifying oxidized multi-walled carbon nanotubes (OMWCNTs) with cerium ions / sodium gluconate and then introducing them into a resin matrix. The OH and COOH groups present in the OMWCNT molecular structure impart a negative charge to the OMWCNT when dispersed in water, allowing cerium cations to adsorb onto the OMWCNT surface. Furthermore, the OMWCNT structure bonds with the cerium cations through π-π interactions, and the negatively charged gluconate molecules interact with the adsorbed cerium cations to form coordination bonds, enabling the OMWCNT to load the cerium ions / sodium gluconate. OMWCNTs provide a high specific surface area and physical barrier while achieving the slow release of cerium ions / sodium gluconate. Cerium ions can interact with hydroxide ions in the cathode area of the metal surface to form a protective precipitation layer. Sodium gluconate interacts with iron ions and cerium ions on the metal substrate to form an insoluble complex. These nanoscale layers can limit the contact between the substrate and the corrosive environment, forming a dual-effect protection with the chelating ability of phytic acid in the boron nitride / PA-MA / EDA hybrid material, thereby improving the overall long-term corrosion resistance. In addition, cerium ions have a strong antioxidant effect and can improve the antioxidant properties of the coating by capturing free radicals, further improving the weather resistance under ultraviolet light.
[0010] The present invention also adds polycaprolactone, which has a flexible polymer chain. The ester bonds and methylene segments in its molecular chain are highly flexible. During the epoxy resin curing process, polycaprolactone is embedded in the epoxy cross-linked network through physical entanglement, providing a certain deformation ability for the overall material, and cooperating with the PA-MA / EDA network to better buffer external stress and improve the overall flexibility of the coating; in addition, in a high temperature environment, the heat absorption properties of boron nitride and OMWCNT are utilized, which can act as a thermal conductor to transfer heat to the surrounding polycaprolactone area more quickly, inducing heat and heating the system. The low-melting-point polycaprolactone melt diffuses to the crack area on the resin surface to fill and repair the microcracks in the resin, avoiding brittle fracture of the coating due to high temperature.
[0011] Optionally, the functionalized boron nitride is obtained by adding 3-aminopropyltriethoxysilane and hydroxylated boron nitride to an ethanol aqueous solution with a volume concentration of 90%, and stirring at 75-85° C. for 10-12 hours.
[0012] The present invention performs surface functionalization treatment on boron nitride. The amino groups or hydroxyl groups on the surface of the treated boron nitride provide reaction anchor points for subsequent bonding with PA-MA / EDA, thereby better achieving the grafting of PA-MA / EDA on the boron nitride surface and improving the grafting efficiency.
[0013] Optionally, the hydroxylated boron nitride is obtained by adding boron nitride nanosheets to a 5 mol / L NaOH solution, stirring and refluxing at 50-60° C. for 2 h, filtering, washing with deionized water for 3-5 times, and vacuum drying at 60-80° C. for 12-24 h.
[0014] The present invention performs hydroxylation treatment on the boron nitride nanosheets to provide reaction anchor points for the grafting of 3-aminopropyltriethoxysilane, thereby forming a stable BO-Si covalent bond.
[0015] Optionally, in step S1, functionalized boron nitride is dispersed in deionized water, ultrasonically treated for 5 to 10 minutes, phytic acid is added and stirred for 5 to 10 minutes, the temperature is adjusted to 65°C, melamine and hexamethylenediamine are added and stirred for 2 to 3 hours, the precipitate is centrifuged, and vacuum dried at 60 to 70°C for 12 to 24 hours to obtain a boron nitride / PA-MA / EDA hybrid material.
[0016] Optionally, in step S2, the oxidized multi-walled carbon nanotubes are added to water, ultrasonically treated for 2 to 5 minutes, cerium nitrate hexahydrate is added, mixed and stirred for 3 to 5 hours under ultrasonic treatment, centrifuged at 3000 rpm for 10 minutes, the supernatant is discarded, the precipitate is washed with deionized water 3 to 5 times to obtain OMWCNT-Ce; OMWCNT-Ce is added to water, ultrasonically treated for 2 to 5 minutes, sodium gluconate is added, mixed and stirred for 2 to 3 hours under ultrasonic treatment, centrifuged at 1200 rpm for 5 minutes, the supernatant is discarded, and the precipitate is washed with deionized water 3 to 5 times to obtain an OMWCNT-Ce-sodium gluconate composite material.
[0017] Optionally, the oxidized multi-walled carbon nanotubes are prepared by adding multi-walled carbon nanotubes to a mixed solution containing sulfuric acid and nitric acid, stirring and heating to 100°C under reflux conditions for 24 hours, adding deionized water and placing in an ice bath, stirring for 40 minutes, standing for 3 days, centrifuging at 4000 rpm for 10 minutes, discarding the supernatant and taking the precipitate, and washing with deionized water 5 times to obtain.
[0018] The present invention uses sulfuric acid and nitric acid to introduce oxygen-containing groups mainly composed of carboxyl and hydroxyl groups on the surface of multi-walled carbon nanotubes, providing active sites for the adsorption of cerium ions / sodium gluconate and improving the loading efficiency of the multi-walled carbon nanotubes.
[0019] Optionally, the solid epoxy resin is hydrogenated bisphenol A epoxy resin, the liquid epoxy resin is bisphenol A epoxy resin; the active diluent is one of allyl glycidyl ether, butyl glycidyl ether, and castor oil polyglycidyl ether; the mixed solvent is propylene glycol methyl ether and butanol; and the curing agent is methyltetrahydrophthalic anhydride and isophorone diamine.
[0020] The present invention uses hydrogenated bisphenol A epoxy resin as a solid resin instead of traditional bisphenol A epoxy resin. Hydrogenated bisphenol A epoxy resin converts the benzene ring into a saturated six-membered ring through catalytic hydrogenation, eliminating conjugated double bonds to block photodegradation reactions and reduce easily oxidized sites, thereby effectively reducing the risk of yellowing of the coating.
[0021] Specifically, the wetting and dispersing agent model is RP-5014, the leveling agent model is EFKA3777, and the defoaming agent model is byk-a530.
[0022] Optionally, in step S3, a wetting dispersant, a pigment, and a barium sulfate are added when adding the liquid epoxy resin, the boron nitride / PA-MA / EDA hybrid material, the OMWCNT-Ce-sodium gluconate composite material, and the polycaprolactone for mixing and stirring, and a leveling agent and a defoaming agent are also added when adding the curing agent and stirring evenly.
[0023] Optionally, in step S3, hydrogenated bisphenol A epoxy resin, active diluent, propylene glycol methyl ether, and butanol are added to a reactor, heated to 50°C, stirred at a high speed of 1200 r / min for 3 to 5 minutes, bisphenol A epoxy resin is added and stirred at a medium speed of 800 to 1000 r / min for 10 to 15 minutes, and boron nitride / PA-MA / EDA hybrid material, OMWCNT-Ce-sodium gluconate composite material, polycaprolactone, and wet The dispersant, pigment, filler and barium sulfate were first stirred at a low speed of 300 r / min for 10 minutes, then the speed was gradually increased to 1500~2000 r / min and stirred at a high speed for 30~45 minutes, cooled to 30°C, and ground and dispersed 3 times. Methyltetrahydrophthalic anhydride and isophorone diamine were added and mixed and stirred at 500 rpm for 20~30 minutes. A leveling agent and a defoaming agent were added and stirred at a low speed of 300 r / min for 10~20 minutes to obtain a high-solid epoxy coating.
[0024] The present invention also provides a high-solids epoxy coating, comprising the following raw materials in parts by mass: 40-55 parts of solid epoxy resin, 8-16 parts of reactive diluent, 10-15 parts of mixed solvent, 15-30 parts of liquid epoxy resin, 15-20 parts of boron nitride / PA-MA / EDA hybrid material, 3-5 parts of OMWCNT-Ce-sodium gluconate composite material, 5-15 parts of polycaprolactone, and 35-50 parts of curing agent; The mixed solvent comprises the following raw materials in parts by mass: 7-10 parts of propylene glycol methyl ether and 3-5 parts of butanol; the curing agent comprises the following raw materials in parts by mass: 15-20 parts of methyltetrahydrophthalic anhydride and 20-30 parts of isophorone diamine.
[0025] The above technical solution of the present invention includes at least the following beneficial effects: 1. This invention utilizes the interaction between the amino groups of phytic acid (PA) and melamine (MA) / hexamethylenediamine (EDA) to form a PA-MA / EDA network, which is then organized on a boron nitride surface. This hybrid material enhances the reactivity of epoxy groups, increases crosslink density, and improves mechanical properties and adhesion. The flexible chains of hexamethylenediamine also mitigate internal stress caused by excessive crosslink density. Boron nitride improves the coating's physical barrier properties, while the chelation effect of phytic acid enhances corrosion protection, delays corrosion, and reduces photocatalytic oxidation reactions, significantly improving the coating's corrosion resistance and weather resistance.
[0026] 2. This invention prepares an OMWCNT-Ce-sodium gluconate composite material. OMWCNTs are modified with cerium ions and sodium gluconate and then incorporated into a resin matrix. The OMWCNTs are loaded with cerium ions and sodium gluconate, allowing for a slow release of the cerium ions, forming a protective precipitate layer that limits the substrate's exposure to corrosive environments. Sodium gluconate forms an insoluble complex with the metal surface, enhancing corrosion resistance. Combined with the chelating effect of phytic acid, this provides dual-effect protection, improving long-term corrosion resistance.
[0027] 3. The present invention incorporates polycaprolactone, whose flexible molecular chains embed into the cross-linked network during the epoxy resin curing process, enhancing the coating's flexibility and deformability. The polycaprolactone synergizes with the PA-MA / EDA network to effectively buffer external stresses. In high-temperature environments, the thermal conductivity of boron nitride and OMWCNT accelerates heat transfer, while the polycaprolactone melt repairs microcracks in the resin, further preventing brittle fracture at high temperatures and improving the coating's high-temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The figure is a histogram of the glossiness of the coating films prepared in the examples of the present invention and the comparative examples before and after UV aging. DETAILED DESCRIPTION
[0029] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention. All other embodiments obtained by ordinary technicians in this field based on the described embodiments of the present invention are within the scope of protection of the present invention.
[0030] Example 1 40 g of boron nitride nanosheets were added to 500 mL of 5 mol / L NaOH solution, stirred and refluxed at 60 °C for 2 h, filtered, washed with deionized water 5 times, and vacuum dried at 80 °C for 24 h to obtain hydroxylated boron nitride; 50 mL of 3-aminopropyltriethoxysilane and 30 g of hydroxylated boron nitride were added to a 90% ethanol aqueous solution and stirred at 85 °C for 12 h to obtain functionalized boron nitride; 30 g of functionalized boron nitride was dispersed in 1000 mL of deionized water, ultrasonically treated for 10 min, and then 25 g of phytic acid (PA) was added and stirred for 10 min. The temperature was adjusted to 65 °C, and 40 g of melamine (MA) and 20 g of hexamethylenediamine (EDA) were added and stirred for 3 h. The precipitate was collected by centrifugation and vacuum dried at 70 °C for 24 h to obtain boron nitride / PA-MA / EDA hybrid material.
[0031] 300 mL of 98% sulfuric acid solution and 100 mL of 65% nitric acid solution were mixed to obtain a mixed solution containing sulfuric acid and nitric acid; 7 g of multi-walled carbon nanotubes (CAS No.: 308068-56-6) were added to 400 mL of the mixed solution containing sulfuric acid and nitric acid, stirred and heated to 100°C under reflux conditions for 24 hours, then 2 L of deionized water was added and placed in an ice bath, stirred for 40 minutes, allowed to stand for 3 days, centrifuged at 4000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 5 times to obtain oxidized multi-walled carbon nanotubes; 6 g of oxidized multi-walled carbon nanotubes (OMWCNT) were added to 1 L of water, ultrasonically treated for 5 minutes, and then 12 g of cerium nitrate hexahydrate was added. The mixture was mixed and stirred for 5 hours under ultrasonic treatment, centrifuged at 3000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 5 times to obtain OMWCNT-Ce; 6 g of oxidized multi-walled carbon nanotubes (OMWCNT) were added to 1 L of water, ultrasonically treated for 5 minutes, and then 12 g of cerium nitrate hexahydrate was added. The mixture was mixed and stirred under ultrasonic treatment for 5 hours, centrifuged at 3000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 5 times to obtain OMWCNT-Ce; OMWCNT-Ce was added to 1 L of water and ultrasonically treated for 5 minutes. Then, 10 g of sodium gluconate was added and mixed and stirred for 3 hours under ultrasonic treatment. The mixture was centrifuged at 1200 rpm for 5 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 5 times to obtain an OMWCNT-Ce-sodium gluconate composite material.
[0032] 55g hydrogenated bisphenol A epoxy resin, 16g castor oil polyglycidyl ether, 7g propylene glycol methyl ether, and 3g butanol were added into the reactor, heated to 50°C, stirred at a high speed of 1200r / min for 5min, 15g liquid bisphenol A epoxy resin was added and stirred at a medium speed of 1000r / min for 15min, 25g boron nitride / PA-MA / EDA hybrid material, 5g OMWCNT-Ce-sodium gluconate composite material, 15g polycaprolactone, 8g pigment filler, and 1g RP-5014 wetting and dispersing agent and 30g barium sulfate were first stirred at a low speed of 300r / min for 10min, then the speed was gradually increased to 2000r / min and stirred at a high speed for 45min. The temperature was lowered to 30℃ and the mixture was ground and dispersed three times. 20g methyltetrahydrophthalic anhydride (CAS No.: 26590-20-5) and 30g isophorone diamine curing agent (CAS No.: 2855-13-2) were added and mixed and stirred at 500rpm for 30min. 0.6g EFKA3777 leveling agent and 0.5g BYK-A530 defoaming agent were added and stirred at a low speed of 300r / min for 20min to prepare a high-solid epoxy coating.
[0033] Example 2 40 g of boron nitride nanosheets were added to 500 mL of 5 mol / L NaOH solution, stirred and refluxed at 55 °C for 2 h, filtered, washed four times with deionized water, and vacuum dried at 70 °C for 18 h to obtain hydroxylated boron nitride; 50 mL of 3-aminopropyltriethoxysilane and 30 g of hydroxylated boron nitride were added to a 90% ethanol aqueous solution and stirred at 80 °C for 11 h to obtain functionalized boron nitride; 30 g of functionalized boron nitride was dispersed in 1000 mL of deionized water, ultrasonically treated for 8 min, and then 20 g of phytic acid (PA) was added and stirred for 8 min. The temperature was adjusted to 65 °C, 30 g of melamine (MA) and 20 g of hexamethylenediamine (EDA) were added and stirred for 2.5 h. The precipitate was collected by centrifugation and vacuum dried at 70 °C for 18 h to prepare boron nitride / PA-MA / EDA hybrid material.
[0034] 300 mL of 98% sulfuric acid solution and 100 mL of 65% nitric acid solution were mixed to obtain a mixed solution containing sulfuric acid and nitric acid; 7 g of multi-walled carbon nanotubes (CAS No.: 308068-56-6) were added to 400 mL of the mixed solution containing sulfuric acid and nitric acid, stirred and heated to 100°C under reflux conditions for 24 hours, then 2 L of deionized water was added and placed in an ice bath, stirred for 40 minutes, allowed to stand for 3 days, centrifuged at 4000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 5 times to obtain oxidized multi-walled carbon nanotubes; 5 g of oxidized multi-walled carbon nanotubes (OMWCNT) were added to 1 L of water, ultrasonically treated for 2 minutes, and then 6 g of cerium nitrate hexahydrate was added. The mixture was mixed and stirred for 3 hours under ultrasonic treatment, centrifuged at 3000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 3 times to obtain OMWCNT-Ce; 5 g of oxidized multi-walled carbon nanotubes (OMWCNT) were added to 1 L of water, ultrasonically treated for 2 minutes, and then 6 g of cerium nitrate hexahydrate was added. The mixture was mixed and stirred for 3 hours under ultrasonic treatment, centrifuged at 3000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 3 times to obtain OMWCNT-Ce; 5 g of OMWCNT-Ce was added to 1 L of water and ultrasonically treated for 2 minutes. Then, 10 g of sodium gluconate was added and mixed and stirred for 2 hours under ultrasonic treatment. The mixture was centrifuged at 1200 rpm for 5 minutes, the supernatant was discarded, and the precipitate was washed three times with deionized water to obtain an OMWCNT-Ce-sodium gluconate composite material.
[0035] 50g hydrogenated bisphenol A epoxy resin, 9g allyl glycidyl ether, 10g propylene glycol methyl ether and 5g butanol were added into the reactor, heated to 50°C, stirred at a high speed of 1200r / min for 4min, 20g liquid bisphenol A epoxy resin was added and stirred at a medium speed of 900r / min for 12min, 20g boron nitride / PA-MA / EDA hybrid material, 4g OMWCNT-Ce-sodium gluconate composite material, 10g polycaprolactone, 7g pigment filler and 0.9g RP-5014 wetting and dispersing agent and 28g barium sulfate were first stirred at a low speed of 300r / min for 10min, then the speed was gradually increased to 1800r / min and stirred at a high speed for 40min. The temperature was cooled to 30℃ and ground and dispersed three times. 18g methyltetrahydrophthalic anhydride (CAS No.: 26590-20-5) and 22g isophorone diamine curing agent (CAS No.: 2855-13-2) were added and mixed and stirred at 500rpm for 25min. 0.5g EFKA3777 leveling agent and 0.4g BYK-A530 defoaming agent were added and stirred at a low speed of 300r / min for 15min to prepare a high-solid epoxy coating.
[0036] Example 3 40 g of boron nitride nanosheets were added to 500 mL of 5 mol / L NaOH solution, stirred and refluxed at 50 °C for 2 h, filtered, washed three times with deionized water, and vacuum dried at 60 °C for 12 h to obtain hydroxylated boron nitride; 50 mL of 3-aminopropyltriethoxysilane and 30 g of hydroxylated boron nitride were added to a 90% ethanol aqueous solution and stirred at 75 °C for 10 h to obtain functionalized boron nitride; 30 g of functionalized boron nitride was dispersed in 1000 mL of deionized water, ultrasonically treated for 5 min, and then 10 g of phytic acid (PA) was added and stirred for 5 min. The temperature was adjusted to 65 °C, 20 g of melamine (MA) and 20 g of hexamethylenediamine (EDA) were added and stirred for 2 h. The precipitate was collected by centrifugation and vacuum dried at 60 °C for 12 h to obtain boron nitride / PA-MA / EDA hybrid material.
[0037] 300 mL of 98% sulfuric acid solution and 100 mL of 65% nitric acid solution were mixed to obtain a mixed solution containing sulfuric acid and nitric acid; 5 g of multi-walled carbon nanotubes (CAS No.: 308068-56-6) were added to 400 mL of the mixed solution containing sulfuric acid and nitric acid, stirred and heated to 100°C under reflux conditions for 24 hours, then 2 L of deionized water was added and placed in an ice bath, stirred for 40 minutes, allowed to stand for 3 days, centrifuged at 4000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 5 times to obtain oxidized multi-walled carbon nanotubes; 4 g of oxidized multi-walled carbon nanotubes (OMWCNT) were added to 1 L of water, ultrasonically treated for 4 minutes, and then 6 g of cerium nitrate hexahydrate was added. The mixture was mixed and stirred for 4 hours under ultrasonic treatment, centrifuged at 3000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 4 times to obtain OMWCNT-Ce; 4 g of oxidized multi-walled carbon nanotubes (OMWCNT) were added to 1 L of water, ultrasonically treated for 4 minutes, and then 6 g of cerium nitrate hexahydrate was added. The mixture was mixed and stirred for 4 hours under ultrasonic treatment, centrifuged at 3000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 4 times to obtain OMWCNT-Ce; OMWCNT-Ce was added to 1 L of water and ultrasonically treated for 4 minutes. Then, 8 g of sodium gluconate was added and mixed and stirred for 2.5 hours under ultrasonic treatment. The mixture was centrifuged at 1200 rpm for 5 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 4 times to obtain an OMWCNT-Ce-sodium gluconate composite material.
[0038] 40g hydrogenated bisphenol A epoxy resin, 8g butyl glycidyl ether, 7g propylene glycol methyl ether and 3g butanol were added into the reactor, heated to 50°C, stirred at a high speed of 1200r / min for 3min, 30g liquid bisphenol A epoxy resin was added and stirred at a medium speed of 800r / min for 10min, 15g boron nitride / PA-MA / EDA hybrid material, 3g OMWCNT-Ce-sodium gluconate composite material, 5g polycaprolactone, 5g pigment filler and 0.8g RP-5014 wetting and dispersing agent and 25g barium sulfate were first stirred at a low speed of 300r / min for 10min, then the speed was gradually increased to 1500r / min and stirred at a high speed for 30min. The temperature was cooled to 30℃ and ground and dispersed three times. 15g methyltetrahydrophthalic anhydride (CAS No.: 26590-20-5) and 20g isophorone diamine curing agent (CAS No.: 2855-13-2) were added and mixed and stirred at 500rpm for 20min. 0.4g EFKA3777 leveling agent and 0.3g BYK-A530 defoaming agent were added and stirred at a low speed of 300r / min for 10min to prepare a high-solid epoxy coating.
[0039] Example 4 40 g of boron nitride nanosheets were added to 500 mL of 5 mol / L NaOH solution, stirred and refluxed at 60 °C for 2 h, filtered, washed three times with deionized water, and vacuum dried at 65 °C for 20 h to obtain hydroxylated boron nitride; 50 mL of 3-aminopropyltriethoxysilane and 30 g of hydroxylated boron nitride were added to a 90% ethanol aqueous solution and stirred at 85 °C for 10 h to obtain functionalized boron nitride; 30 g of functionalized boron nitride was dispersed in 1000 mL of deionized water, ultrasonically treated for 10 min, and then 10 g of phytic acid (PA) was added and stirred for 5 min. The temperature was adjusted to 65 °C, 25 g of melamine (MA) and 20 g of hexamethylenediamine (EDA) were added and stirred for 2.5 h. The precipitate was collected by centrifugation and vacuum dried at 65 °C for 22 h to obtain boron nitride / PA-MA / EDA hybrid material.
[0040] 300 mL of 98% sulfuric acid solution and 100 mL of 65% nitric acid solution were mixed to obtain a mixed solution containing sulfuric acid and nitric acid; 10 g of multi-walled carbon nanotubes (CAS No.: 308068-56-6) were added to 400 mL of the mixed solution containing sulfuric acid and nitric acid, stirred and heated to 100°C under reflux conditions for 24 hours, then 2 L of deionized water was added and placed in an ice bath, stirred for 40 minutes, allowed to stand for 3 days, centrifuged at 4000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed 5 times with deionized water to obtain oxidized multi-walled carbon nanotubes; 6 g of oxidized multi-walled carbon nanotubes (OMWCNT) were added to 1 L of water, ultrasonically treated for 5 minutes, and then 10 g of cerium nitrate hexahydrate was added. The mixture was mixed and stirred for 3 hours under ultrasonic treatment, centrifuged at 3000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed 5 times with deionized water to obtain OMWCNT-Ce; 6 g of oxidized multi-walled carbon nanotubes (OMWCNT) were added to 1 L of water, ultrasonically treated for 5 minutes, and then 10 g of cerium nitrate hexahydrate was added. The mixture was mixed and stirred for 3 hours under ultrasonic treatment, centrifuged at 3000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed 5 times with deionized water to obtain OMWCNT-Ce; OMWCNT-Ce was added to 1 L of water and ultrasonically treated for 3 minutes. Then, 12 g of sodium gluconate was added and mixed and stirred for 2 hours under ultrasonic treatment. The mixture was centrifuged at 1200 rpm for 5 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 5 times to obtain an OMWCNT-Ce-sodium gluconate composite material.
[0041] 45g hydrogenated bisphenol A epoxy resin, 12g castor oil polyglycidyl ether, 10g propylene glycol methyl ether, and 4g butanol were added into the reactor, heated to 50°C, stirred at a high speed of 1200r / min for 5min, 25g liquid bisphenol A epoxy resin was added and stirred at a medium speed of 900r / min for 10min, 18g boron nitride / PA-MA / EDA hybrid material, 5g OMWCNT-Ce-sodium gluconate composite material, 12g polycaprolactone, 7g pigment filler, and 1g RP-5014 wetting and dispersing agent and 26g barium sulfate were first stirred at a low speed of 300r / min for 10min, then the speed was gradually increased to 1800r / min and stirred at a high speed for 35min. The temperature was cooled to 30℃ and ground and dispersed three times. 18g methyltetrahydrophthalic anhydride (CAS No.: 26590-20-5) and 26g isophorone diamine curing agent (CAS No.: 2855-13-2) were added and mixed and stirred at 500rpm for 25min. 0.4g EFKA3777 leveling agent and 0.5g BYK-A530 defoaming agent were added and stirred at a low speed of 300r / min for 16min to prepare a high-solid epoxy coating.
[0042] Example 5 40 g of boron nitride nanosheets were added to 500 mL of 5 mol / L NaOH solution, stirred and refluxed at 50 °C for 2 h, filtered, washed three times with deionized water, and vacuum dried at 60 °C for 12 h to obtain hydroxylated boron nitride; 50 mL of 3-aminopropyltriethoxysilane and 30 g of hydroxylated boron nitride were added to a 90% ethanol aqueous solution and stirred at 85 °C for 10 h to obtain functionalized boron nitride; 30 g of functionalized boron nitride was dispersed in 1000 mL of deionized water, ultrasonically treated for 5 min, and then 10 g of phytic acid (PA) was added and stirred for 5 min. The temperature was adjusted to 65 °C, and 20 g of melamine (MA) and 20 g of hexamethylenediamine (EDA) were added and stirred for 3 h. The precipitate was collected by centrifugation and vacuum dried at 60 °C for 12 h to obtain boron nitride / PA-MA / EDA hybrid material.
[0043] 300 mL of 98% sulfuric acid solution and 100 mL of 65% nitric acid solution were mixed to obtain a mixed solution containing sulfuric acid and nitric acid; 5 g of multi-walled carbon nanotubes (CAS No.: 308068-56-6) were added to 400 mL of the mixed solution containing sulfuric acid and nitric acid, stirred and heated to 100°C under reflux conditions for 24 hours, then 2 L of deionized water was added and placed in an ice bath, stirred for 40 minutes, allowed to stand for 3 days, centrifuged at 4000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 5 times to obtain oxidized multi-walled carbon nanotubes; 4 g of oxidized multi-walled carbon nanotubes (OMWCNT) were added to 1 L of water, ultrasonically treated for 3 minutes, and then 6 g of cerium nitrate hexahydrate was added. The mixture was mixed and stirred for 4 hours under ultrasonic treatment, centrifuged at 3000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 4 times to obtain OMWCNT-Ce; 4 g of oxidized multi-walled carbon nanotubes (OMWCNT) were added to 1 L of water, ultrasonically treated for 3 minutes, and then 6 g of cerium nitrate hexahydrate was added. The mixture was mixed and stirred under ultrasonic treatment for 4 hours, centrifuged at 3000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 4 times to obtain OMWCNT-Ce; OMWCNT-Ce was added to 1 L of water and ultrasonically treated for 3 minutes. Then, 8 g of sodium gluconate was added and mixed and stirred for 2.5 hours under ultrasonic treatment. The mixture was centrifuged at 1200 rpm for 5 minutes, the supernatant was discarded, and the precipitate was washed three times with deionized water to obtain an OMWCNT-Ce-sodium gluconate composite material.
[0044] 55g hydrogenated bisphenol A epoxy resin, 10g butyl glycidyl ether, 7g propylene glycol methyl ether and 5g butanol were added into the reactor, heated to 50°C, stirred at a high speed of 1200r / min for 5min, 15g liquid bisphenol A epoxy resin was added and stirred at a medium speed of 800r / min for 15min, 15g boron nitride / PA-MA / EDA hybrid material, 3g OMWCNT-Ce-sodium gluconate composite material, 15g polycaprolactone, 8g pigment filler and 0.8g RP-5014 wetting and dispersing agent and 25g barium sulfate were first stirred at a low speed of 300r / min for 10min, then the speed was gradually increased to 1500r / min and stirred at a high speed for 45min. The temperature was lowered to 30℃ and the mixture was ground and dispersed three times. 20g methyltetrahydrophthalic anhydride (CAS No.: 26590-20-5) and 20g isophorone diamine curing agent (CAS No.: 2855-13-2) were added and mixed and stirred at 500rpm for 20min. 0.4g EFKA3777 leveling agent and 0.3g BYK-A530 defoaming agent were added and stirred at a low speed of 300r / min for 10min to prepare a high-solid epoxy coating.
[0045] Example 6 40 g of boron nitride nanosheets were added to 500 mL of 5 mol / L NaOH solution, stirred and refluxed at 60 °C for 2 h, filtered, washed three times with deionized water, and vacuum dried at 80 °C for 12 h to obtain hydroxylated boron nitride; 50 mL of 3-aminopropyltriethoxysilane and 30 g of hydroxylated boron nitride were added to a 90% ethanol aqueous solution and stirred at 80 °C for 12 h to obtain functionalized boron nitride; 30 g of functionalized boron nitride was dispersed in 1000 mL of deionized water, ultrasonically treated for 10 min, and then 18 g of phytic acid (PA) was added and stirred for 5 min. The temperature was adjusted to 65 °C, and 35 g of melamine (MA) and 20 g of hexamethylenediamine (EDA) were added and stirred for 2 h. The precipitate was collected by centrifugation and vacuum dried at 70 °C for 12 h to obtain boron nitride / PA-MA / EDA hybrid material.
[0046] 300 mL of 98% sulfuric acid solution and 100 mL of 65% nitric acid solution were mixed to obtain a mixed solution containing sulfuric acid and nitric acid; 7 g of multi-walled carbon nanotubes (CAS No.: 308068-56-6) were added to 400 mL of the mixed solution containing sulfuric acid and nitric acid, stirred and heated to 100°C under reflux conditions for 24 hours, then 2 L of deionized water was added and placed in an ice bath, stirred for 40 minutes, allowed to stand for 3 days, centrifuged at 4000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 5 times to obtain oxidized multi-walled carbon nanotubes; 6 g of oxidized multi-walled carbon nanotubes (OMWCNT) were added to 1 L of water, ultrasonically treated for 2 minutes, and then 10 g of cerium nitrate hexahydrate was added. The mixture was mixed and stirred for 5 hours under ultrasonic treatment, centrifuged at 3000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 3 times to obtain OMWCNT-Ce; 6 g of oxidized multi-walled carbon nanotubes (OMWCNT) were added to 1 L of water, ultrasonically treated for 2 minutes, and then 10 g of cerium nitrate hexahydrate was added. The mixture was mixed and stirred under ultrasonic treatment for 5 hours, centrifuged at 3000 rpm for 10 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 3 times to obtain OMWCNT-Ce; OMWCNT-Ce was added to 1 L of water and ultrasonically treated for 5 minutes. Then, 10 g of sodium gluconate was added and mixed and stirred for 2 hours under ultrasonic treatment. The mixture was centrifuged at 1200 rpm for 5 minutes, the supernatant was discarded, and the precipitate was washed with deionized water 5 times to obtain an OMWCNT-Ce-sodium gluconate composite material.
[0047] 50g hydrogenated bisphenol A epoxy resin, 15g castor oil polyglycidyl ether, 8g propylene glycol methyl ether and 5g butanol were added into the reactor, heated to 50°C, stirred at a high speed of 1200r / min for 3min, 20g liquid bisphenol A epoxy resin was added and stirred at a medium speed of 1000r / min for 10min, 18g boron nitride / PA-MA / EDA hybrid material, 5g OMWCNT-Ce-sodium gluconate composite material, 15g polycaprolactone, 5g pigment filler and 1g RP-5014 wetting and dispersing agent and 25g barium sulfate were first stirred at a low speed of 300r / min for 10min, then the speed was gradually increased to 2000r / min and stirred at a high speed for 30min. The temperature was lowered to 30℃ and the mixture was ground and dispersed three times. 15g methyltetrahydrophthalic anhydride (CAS No.: 26590-20-5) and 30g isophorone diamine curing agent (CAS No.: 2855-13-2) were added and mixed and stirred at 500rpm for 30min. 0.4g EFKA3777 leveling agent and 0.5g BYK-A530 defoaming agent were added and stirred at a low speed of 300r / min for 10min to prepare a high-solid epoxy coating.
[0048] The present invention also carried out comparative examples and related tests.
[0049] Comparative Example 1 Compared with Example 1, the only difference is that the boron nitride / PA-MA / EDA hybrid material is not added, and the other preparation methods and components are exactly the same, and a high-solid epoxy coating is finally prepared.
[0050] Comparative Example 2 Compared with Example 1, the only difference is that polycaprolactone is not added. The other preparation methods and components are exactly the same, and a high-solid epoxy coating is finally prepared.
[0051] Comparative Example 3 Compared with Example 1, the only difference is that the OMWCNT-Ce-sodium gluconate composite material is not added. The other preparation methods and components are exactly the same, and a high-solid epoxy coating is finally prepared.
[0052] Performance testing The high-solid epoxy coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to basic performance tests including mixing viscosity, non-volatile content, coating film drying time, flexibility, impact resistance, and adhesion.
[0053] The high solid epoxy coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were used to determine the non-volatile content of the coatings by measuring the dry coating density according to the national standard GB-T9272-2007 for paints and varnishes. The high-solid epoxy coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were sprayed onto the surface of a tinplate that meets the requirements of the national standard GB / T9271-2008 using a spray gun at a pressure of 0.2 MPa for 30 seconds. After spraying, the coating samples were dried at 80° C. The impact resistance of the coating samples was measured according to the method of the national standard GBT1732-2020 for determining the impact resistance of paint films; the flexibility of the coating samples was measured according to the test method of the national standard GB / T6742-2007 for the bending test (cylindrical mandrel) for paints and varnishes; and the adhesion of the coating samples was measured according to the test method of the national standard GBT9286-2021 for the cross-cut test for paints and varnishes. The test results of the non-volatile content of the above coatings and the flexibility, impact resistance and adhesion of the coating samples are shown in Table 1.
[0054] As can be seen from Table 1, the high-solids epoxy coatings prepared in Examples 1 to 6 of the present invention have a solid content of ≥80% and a low VOC content. In addition, compared with Comparative Examples 1 to 3, the flexibility, impact resistance, and adhesion of the coating samples prepared using Examples 1 to 6 are significantly improved.
[0055] According to the data analysis in Table 1, compared with Comparative Example 1, the addition of boron nitride / PA-MA / EDA hybrid material in Example 1 significantly improves flexibility, impact resistance and adhesion; compared with Example 1, Comparative Example 2 does not add polycaprolactone, and the flexibility is significantly reduced, further affecting the impact resistance; compared with Example 1, Comparative Example 3 lacks the OMWCNT-Ce-sodium gluconate composite material, which has a certain impact on the impact resistance.
[0056] The coating film samples prepared using the high-solid epoxy coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were tested for corrosion resistance and weather resistance.
[0057] First, a uniformly mixed high-solids coating was sprayed and dried three times to form a coating film with a thickness of approximately 100 μm on the surface of a tinplate. A salt spray test was performed in accordance with the national standard GB-T1771-2007, Determination of Neutral Salt Spray Resistance of Paints and Varnishes; an acid and alkali resistance test was performed in accordance with the national standard GBT9274-1988, Determination of Liquid Medium Resistance of Paints and Varnishes; and a water resistance test was performed in accordance with the national standard GB / T1733-1993, Determination of Water Resistance of Paint Films. The corrosion resistance of the coating sample was evaluated based on the experimental results of the salt spray test, water resistance, and acid and alkali resistance. The weather resistance of the coatings prepared using Examples 1 to 6 and Comparative Examples 1 to 3 was evaluated by yellowing resistance and the glossiness of the coatings before and after an artificial accelerated UV aging test. The artificial accelerated UV aging test was conducted according to the national standard GB / T 23987-2009 for artificial weathering of paint and varnish coatings by exposure to fluorescent UV light and water. A Q235 steel plate was selected as the substrate. The coating sample preparation process described above was used to prepare a coating with a thickness of approximately 100 μm. The yellowing index of the coating sample was determined according to the standard ASTM / E313-2010. The coating sample was then subjected to an artificial accelerated UV aging test. The artificial accelerated UV aging test conditions were: a UVA-340 lamp with an irradiance of 0.89 W / m 2 ×nm, exposure period 8h drying, blackboard temperature 60℃, 4h condensation, blackboard temperature 50℃, test time 100h; after the test, the glossiness of the sample was tested. The glossiness comparison of the coating sample before and after the test is shown in the figure. Figure 1 ; The salt spray resistance of the coating films prepared using Examples 1 to 6 and Comparative Examples 1 to 3 is shown in Table 2, and the acid and alkali resistance, water resistance, and yellowing index test results are shown in Table 3.
[0058] From Table 2, Table 3 and Figure 1It can be seen that the corrosion resistance and weather resistance of the coating films prepared using the high-solid epoxy coatings prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 3 are significantly improved compared to Comparative Examples 1 to 3.
[0059] According to the data in Table 2 and Table 3, it can be seen that compared with Comparative Example 1, the addition of boron nitride / PA-MA / EDA hybrid material in Example 1 plays a role of physical barrier and chemical passivation, and the salt spray resistance is significantly improved. The improvement of adhesion also plays a synergistic role in corrosion resistance, and the corrosion resistance is also significantly improved; compared with Comparative Example 3, the addition of OMWCNT-Ce-sodium gluconate composite material in Example 1 plays a certain antioxidant effect, reduces yellowing, and significantly improves yellowing resistance. Cerium ions and sodium gluconate also play a good corrosion inhibition effect, and the salt spray resistance and acid and alkali corrosion resistance are significantly improved. Figure 1 The bar graph of the gloss of the coating films before and after the artificial accelerated UV aging test is shown in FIG. 1 . It can be seen that the gloss of the coating films prepared using the high-solid epoxy coatings prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 3 remains in a good state after the artificial accelerated UV aging test, while the gloss of Comparative Example 1 and Comparative Example 3 decreases significantly.
[0060] In summary, the high-solids epoxy coatings prepared in Examples 1 to 6 of the present invention not only have high solids and low VOC content, but also have good flexibility and impact resistance, good adhesion to the substrate, and good corrosion resistance and weather resistance.
[0061] The above is a preferred embodiment of the present invention. Those skilled in the art may make several improvements and modifications without departing from the principles of the present invention. These improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a high-solid epoxy coating, characterized in that: The steps include: S1. Functionalized boron nitride is dispersed in water, ultrasonically treated, phytic acid is added and stirred, the temperature is increased, melamine and hexamethylenediamine are added and stirred, the precipitate is collected by centrifugation, and vacuum dried to prepare a boron nitride / PA-MA / EDA hybrid material; S2, adding the oxidized multi-walled carbon nanotubes into water for ultrasonic treatment, adding cerium nitrate hexahydrate and sodium gluconate, mixing, centrifuging to obtain a precipitate, and washing to obtain an OMWCNT-Ce-sodium gluconate composite material; S3. Add solid epoxy resin, active diluent and mixed solvent into the reactor, heat and stir, add liquid epoxy resin, boron nitride / PA-MA / EDA hybrid material, OMWCNT-Ce-sodium gluconate composite material and polycaprolactone, mix and stir, grind and disperse, add curing agent and stir evenly to obtain high-solid epoxy coating.
2. The method for preparing a high-solid epoxy coating according to claim 1, wherein: The functionalized boron nitride is obtained by adding 3-aminopropyltriethoxysilane and hydroxylated boron nitride to an ethanol aqueous solution with a volume concentration of 90%, and stirring at 75-85° C. for 10-12 hours.
3. The method for preparing a high-solid epoxy coating according to claim 2, wherein: The hydroxylated boron nitride is obtained by adding boron nitride nanosheets to a 5 mol / L NaOH solution, stirring and refluxing at 50-60° C. for 2 hours, filtering, washing with deionized water for 3-5 times, and vacuum drying at 60-80° C. for 12-24 hours.
4. The method for preparing a high-solid epoxy coating according to claim 1, wherein: In step S1, functionalized boron nitride is dispersed in deionized water, ultrasonically treated for 5-10 minutes, phytic acid is added and stirred for 5-10 minutes, the temperature is adjusted to 65° C., melamine and hexamethylenediamine are added and stirred for 2-3 hours, the precipitate is centrifuged, and vacuum dried at 60-70° C. for 12-24 hours to obtain a boron nitride / PA-MA / EDA hybrid material.
5. The method for preparing a high-solid epoxy coating according to claim 1, wherein: In the step S2, the oxidized multi-walled carbon nanotubes are added to water, ultrasonically treated for 2 to 5 minutes, and then cerium nitrate hexahydrate is added. The mixture is mixed and stirred for 3 to 5 hours under ultrasonic treatment, centrifuged at 3000 rpm for 10 minutes, the supernatant is discarded, and the precipitate is washed with deionized water 3 to 5 times to obtain OMWCNT-Ce; the OMWCNT-Ce is added to water, ultrasonically treated for 2 to 5 minutes, and then sodium gluconate is added. The mixture is mixed and stirred for 2 to 3 hours under ultrasonic treatment, centrifuged at 1200 rpm for 5 minutes, the supernatant is discarded, and the precipitate is washed with deionized water 3 to 5 times to obtain an OMWCNT-Ce-sodium gluconate composite material.
6. The method for preparing a high-solid epoxy coating according to claim 1, wherein: The oxidized multi-walled carbon nanotubes are prepared by adding multi-walled carbon nanotubes to a mixed solution containing sulfuric acid and nitric acid, stirring and heating to 100°C under reflux conditions for 24 hours, adding deionized water and placing in an ice bath, stirring for 40 minutes, standing for 3 days, centrifuging at 4000 rpm for 10 minutes, discarding the supernatant, and taking the precipitate, which is washed with deionized water five times to obtain the obtained product.
7. The method for preparing a high-solid epoxy coating according to claim 1, wherein: The solid epoxy resin is hydrogenated bisphenol A epoxy resin, the liquid epoxy resin is bisphenol A epoxy resin; the active diluent is one of allyl glycidyl ether, butyl glycidyl ether, and castor oil polyglycidyl ether; the mixed solvent is propylene glycol methyl ether and butanol; and the curing agent is methyltetrahydrophthalic anhydride and isophorone diamine.
8. The method for preparing a high-solid epoxy coating according to claim 1, wherein: In step S3, a wetting and dispersing agent, a pigment and filler, and barium sulfate are added when the liquid epoxy resin, the boron nitride / PA-MA / EDA hybrid material, the OMWCNT-Ce-sodium gluconate composite material, and the polycaprolactone are added and mixed. A leveling agent and a defoaming agent are also added when the curing agent is added and mixed.
9. The method for preparing a high-solid epoxy coating according to claim 1, wherein: In the step S3, hydrogenated bisphenol A epoxy resin, reactive diluent, propylene glycol methyl ether, and butanol are added to a reactor, the temperature is raised to 50° C., and the mixture is stirred at a high speed of 1200 r / min for 3-5 minutes. Bisphenol A epoxy resin is added and stirred at a medium speed of 800-1000 r / min for 10-15 minutes. Boron nitride / PA-MA / EDA hybrid material, OMWCNT-Ce-sodium gluconate composite material, polycaprolactone, wetting dispersant, pigment and filler, and barium sulfate are added and stirred at a low speed of 300 r / min for 10 minutes. The speed is then gradually increased to 1500-2000 r / min and stirred at a high speed for 30-45 minutes. The mixture is cooled to 30° C. and ground and dispersed three times. Methyltetrahydrophthalic anhydride and isophorone diamine are added and mixed and stirred at 500 rpm for 20-30 minutes. A leveling agent and a defoamer are added and stirred at a low speed of 300 r / min for 10-20 minutes to prepare a high-solid epoxy coating.
10. A high solid epoxy coating, characterized in that: Prepared by the preparation method of a high-solid epoxy coating according to any one of claims 1 to 9, comprising the following raw materials in parts by weight: 40 to 55 parts of solid epoxy resin, 8 to 16 parts of reactive diluent, 10 to 15 parts of mixed solvent, 15 to 30 parts of liquid epoxy resin, 15 to 20 parts of boron nitride / PA-MA / EDA hybrid material, 3 to 5 parts of OMWCNT-Ce-sodium gluconate composite material, 5 to 15 parts of polycaprolactone, and 35 to 50 parts of curing agent; The mixed solvent comprises the following raw materials in parts by mass: 7-10 parts of propylene glycol methyl ether and 3-5 parts of butanol; the curing agent comprises the following raw materials in parts by mass: 15-20 parts of methyltetrahydrophthalic anhydride and 20-30 parts of isophorone diamine.
Citation Information
Patent Citations
Corrosion-resistant pipeline coating material and preparation method thereof
CN118852951A